Continued proportional age shift of confirmed positive COVID-19 incidence over time to children and young adults: Washington State March-August 2020. - Judith Malmgren; Boya Guo; Henry G Kaplan (PLoS ONE)
Background As the coronavirus (COVID-19) epidemic passed initial infection peak in Washington State, phased re-opening lifted stay-at-home orders and restrictions leading to increased non-essential work, social activities and gathering, especially among younger persons. Methods A longitudinal cohort analysis of Washington State Department of Health COVID-19 confirmed case age distribution 1) March-April 2020 (N = 13,934) and 2) March-August 2020 (N = 76,032) for proportional change over time using chi square tests for significance. Results From March 1st to April 19, 2020 COVID-19 age distribution shifted with a 10% decline in cases age 60 years and older and a 20% increase in age 0-19/20-39 years (chi-square = 223.10, p < .001). Number of cases over the initial analysis period were 0-19 years n = 515, 20-39 years n = 4078, 40-59 years n = 4788, 60-79 years n = 3221, 80+ years n = 1332. After the peak (March 22, 2020), incidence declined in older age groups and increased among age 0-19 and 20-39 age groups from 20% to 40% of total cases by April 19 and 50% by May 3. During this time testing expanded with more testing among older age groups and less testing among younger age groups while case positivity shifted young. Percent positive cases age 0-19/20-39 years through August 2020 increased to a consistent average of 60% [age 0-19 increased to 19% (N = 10257), age 20-39 increased to 42% (N = 30215)]. Conclusions An increased sustained proportion of COVID-19 incidence is present among children (age 0-19) and young adults (age 20-39) indicating an elevated role in disease spread during the epidemic creating a possible reservoir of disease with spillover risk to more vulnerable older persons and those with comorbid conditions. Media savvy age-appropriate messaging to enhance mitigation compliance among less vulnerable, more mobile and lower priority vaccination age groups will be a continued necessity and priority to reduce overall population incidence.